Training on Diverse, Nutritious, Balanced, and Safe Menus Based on Local Food in Surakarta - Suswadi; Agung Prasetyo (Journal of Community Capacity Empowerment, 2023)
The purpose of organizing the Local Food-Based Menu Training is to: 1. Enhance the community's understanding in applying the principles of Diverse, Nutritious, Balanced, and Safe by utilizing local food. 2. Foster creativity and innovation in the development of commercially valuable local food. Training for the development of balanced nutrition menus for mothers is highly essential, considering that mothers play a pivotal role in improving family nutrition. The menu planning training was conducted in June 2023, targeting a group of 20 mothers who are members of the Surakarta Family Welfare Association Pokja 3. The evaluation results using a pre-test questionnaire show that the cognitive ability of the mothers had an average pre-test score of 72.90% and a post-test score after training of 80.83%. In terms of attitude, the pre-test score was 28.61, which increased to 32.93 in the post-test after the training.